Carbon-based catalysts for Fischer-Tropsch synthesis - Chen, Yanping; Wei, Jiatong; Duyar, Melis S; Ordomsky, Vitaly V; Khodakov, Andrei Y; Liu, Jian (Chemical Society reviews, 2021)
Fischer-Tropsch synthesis (FTS) is an essential approach to convert coal, biomass, and shale gas into fuels and chemicals, such as lower olefins, gasoline, diesel, and so on. In recent years, there has been increasing motivation to deploy FTS at commercial scales which has been boosting the discovery of high performance catalysts. In particular, the importance of support in modulating the activity of metals has been recognized and carbonaceous materials have attracted attention as supports for FTS. In this review, we summarised the substantial progress in the preparation of carbon-based catalysts for FTS by applying activated carbon (AC), carbon nanotubes (CNTs), carbon nanofibers (CNFs), carbon spheres (CSs), and metal-organic frameworks (MOFs) derived carbonaceous materials as supports. A general assessment of carbon-based catalysts for FTS, concerning the support and metal properties, activity and products selectivity, and their interactions is systematically discussed. Finally, current challenges and future trends in the development of carbon-based catalysts for commercial utilization in FTS are proposed. The substantial progress of application of carbon-based catalysts in FTS has been systematically summarized and discussed in this review article.